2020
DOI: 10.1007/s11207-020-01714-z
|View full text |Cite
|
Sign up to set email alerts
|

On the Radial and Longitudinal Variation of a Magnetic Cloud: ACE, Wind, ARTEMIS and Juno Observations

Abstract: We present observations of the same magnetic cloud made near Earth by the Advance Composition Explorer (ACE), Wind, and the Acceleration, Reconnection, Turbulence and Electrodynamics of the Moon’s Interaction with the Sun (ARTEMIS) mission comprising the Time History of Events and Macroscale Interactions during Substorms (THEMIS) B and THEMIS C spacecraft, and later by Juno at a distance of 1.2 AU. The spacecraft were close to radial alignment throughout the event, with a longitudinal separation of $3.6^{\circ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 93 publications
0
33
0
Order By: Relevance
“…The small longitudinal (within 5 • ) and latitudinal separation between Solar Orbiter, Wind, and BepiColombo during the passage of the CME provides an opportunity to study the radial evolution of the CME using in situ measurements of the magnetic field. However, caution must still applied when interpreting results as significant differences in CME magnetic flux rope properties have previously been observed over small longitudinal separations (Kilpua et al 2011;Winslow et al 2016;Davies et al 2020) and therefore differences in observations and properties may also be due to spatial variation of the CME. Similarly to the KFR and 3DCORE models, this analysis focuses on the section of the flux rope which is unperturbed (the UMFR) by the interaction with the following higher speed stream and the phys-Article number, page 5 of 11 A&A proofs: manuscript no.…”
Section: Radial Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The small longitudinal (within 5 • ) and latitudinal separation between Solar Orbiter, Wind, and BepiColombo during the passage of the CME provides an opportunity to study the radial evolution of the CME using in situ measurements of the magnetic field. However, caution must still applied when interpreting results as significant differences in CME magnetic flux rope properties have previously been observed over small longitudinal separations (Kilpua et al 2011;Winslow et al 2016;Davies et al 2020) and therefore differences in observations and properties may also be due to spatial variation of the CME. Similarly to the KFR and 3DCORE models, this analysis focuses on the section of the flux rope which is unperturbed (the UMFR) by the interaction with the following higher speed stream and the phys-Article number, page 5 of 11 A&A proofs: manuscript no.…”
Section: Radial Evolutionmentioning
confidence: 99%
“…separated by less than 5 • in longitude and separated by more than 0.2 AU in heliocentric distance are relatively rare but provide valuable insight into the properties, rotation, expansion, and interaction with other features of the solar wind environment as the ICME propagates (e.g. Good et al 2015Good et al , 2018Winslow et al 2016;Kilpua et al 2019;Lugaz et al 2019;Davies et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a focus has been placed on the study of multi-point events, namely, ICMEs that are observed in situ by multiple spacecraft (Möstl et al 2009a;Kilpua et al 2009;Good et al 2019;Davies et al 2020;Salman et al 2020) in an attempt to gain a better global understanding of ICME structure and their evolution. Unfortunately, such events are inherently rare due to the limited number of spacecraft with the onboard magnetometers in different solar orbits within similar time frames.…”
Section: Introductionmentioning
confidence: 99%
“…CME evolution and propagation in the heliosphere is still one of the critical areas of research. In this collection, there are several studies that span from a case event analysis, data analysis, 3D simulation, theoretical understanding of the physical processes associated with the evolution, and identification of the internal structure based on artificial intelligence techniques (Davies et al, 2020;Balmaceda et al, 2020;Desai et al, 2020;Florido-Llinas, Nieves-Chinchilla, and Linton, 2020;dos Santos et al, 2020). As stated by Balmaceda et al (2020) (Editor's choice), a proper characterization of the kinematics of CMEs is important not only for practical purposes, i.e.…”
mentioning
confidence: 99%
“…Thus, their study focused on the observations obtained with COR2 onboard the Solar Terrestrial Relations Observatory (STEREO) from 2007 to 2014 to investigate the self-similarity assumption as a function of the heliocentric distance of the CME events. Davies et al (2020) reported the case of a multipoint-observed magnetic cloud by the Advanced Composition Explorer (ACE), Wind, the Acceleration, Reconnection, Turbulence and Electrodynamics of the Moon's Interaction with the Sun (ARTEMIS), and Juno satellites on 25 October 2011. This singular opportunity allowed the exploration of the radial and longitudinal variation of the internal properties of the magnetic cloud.…”
mentioning
confidence: 99%